Analisis Pengembangan Badan Usaha Milik Desa (Studi Pada BUMDes Kanie Kabupaten Sidenreng Rappang) - helmalia helmalia; Herman Dema; Barisan Barisan (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the potential and development strategies of the Village-Owned Enterprise (BUMDes) in Kanie Village, Sidenreng Rappang Regency. Although the village has established a BUMDes unit focusing on office supplies, its management has not been optimal and does not yet reflect the village’s full potential. This research employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles and Huberman model and assisted by NVivo 12 Plus software. The findings reveal six major potentials in Kanie Village: natural resources, human resources, economic potential, socio-cultural aspects, institutional capacity, and geography. However, most of these potentials have not been fully utilized by BUMDes. The recommended development strategies include community empowerment, increased transparency, provision of capital and infrastructure, optimization of local resources, and collaboration with third parties. This study highlights the importance of a comprehensive, locallybased approach to ensure that BUMDes can develop sustainably and contribute significantly to improving the welfare of rural communities.